The Influence of Kinetic Facade Design on Visual Comfort in Humid Tropical Climate - Angga Ardiansyah; Muhammad Yusuf S; Fariz Ahsan Maulana (GLOBAL SCIENTS PUBLISHER, 2026)
Natural lighting plays an important role in achieving visual comfort and energy efficiency in office buildings, particularly in humid tropical climates where excessive solar radiation often leads to glare and uneven illumination. This study aims to examine the influence of kinetic facade design on visual comfort using a systematic literature review approach. Relevant scientific articles related to adaptive facades and daylighting performance were analyzed to identify key design strategies and performance outcomes. The findings show that kinetic facade systems are capable of improving daylight distribution, reducing glare intensity, and maintaining more stable indoor illumination levels compared to conventional static facades. Several adaptive mechanisms, such as rotating panels, folding systems, and sensor-based controls, demonstrate effective real-time responses to varying solar conditions, resulting in improved visual comfort performance. This study contributes by synthesizing existing research to highlight the most effective kinetic facade strategies for humid tropical climates and by providing a conceptual basis for their application in office building design to enhance visual comfort and environmental responsiveness.